2023
DOI: 10.1021/acs.chemrev.3c00459
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Phase Engineering of Nanomaterials

Qinbai Yun,
Yiyao Ge,
Zhenyu Shi
et al.

Abstract: As a key structural parameter, phase depicts the arrangement of atoms in materials. Normally, a nanomaterial exists in its thermodynamically stable crystal phase. With the development of nanotechnology, nanomaterials with unconventional crystal phases, which rarely exist in their bulk counterparts, or amorphous phase have been prepared using carefully controlled reaction conditions. Together these methods are beginning to enable phase engineering of nanomaterials (PEN), i.e. , the synthesis of nanomaterials w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 1,351 publications
(3,304 reference statements)
0
4
0
Order By: Relevance
“…257,391−393 TMDs used in reported twisted bilayers are still conventional phase. With the fast development of phase engineering of TMDs, 15,16,32,42,69,112,394 twisted unconventional/metastable-phase TMD bilayers or multilayers could be fabricated and used for exploration of twisted layerdependent new phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…257,391−393 TMDs used in reported twisted bilayers are still conventional phase. With the fast development of phase engineering of TMDs, 15,16,32,42,69,112,394 twisted unconventional/metastable-phase TMD bilayers or multilayers could be fabricated and used for exploration of twisted layerdependent new phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Although twisted TMD bilayers have attracted intensive research attention after the unconventional superconductivity was observed in magic-angle graphene superlattices. , TMDs used in reported twisted bilayers are still conventional phase. With the fast development of phase engineering of TMDs, ,,,,,, twisted unconventional/metastable-phase TMD bilayers or multilayers could be fabricated and used for exploration of twisted layer-dependent new phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Nanostructural metallic materials are a pioneering research field of modern nanoscience. The advanced technologies (e.g., aberration-corrected transmission electron microscopy and three-dimensional atom probe tomography) contribute significantly to the fine phase-controlling of nanostructural metallic materials. , The sophisticated designs of phase size, phase distribution, and phase transformation are disclosed as a significant pathway to change the physicochemical properties, such as the near-theoretical strength achieved by the dual-phase glass-crystal structure, the extremely stable catalysis shown by the Turing catalyst with a specific phase configuration, and the unconventional phase transformation of nanomaterials. This progress inspired material scientists as to the importance of phase engineering that would provide new insights and scientific implications for the development of high-performance materials. Indeed, the concept of phase in structural materials is sometimes different from nanomaterials, primarily due to differences in their scale, structural characteristics, and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the manufacturing of metastable nanomaterials encounters formidable challenges, such as limited intrinsic structures, particle agglomeration, poor activity and stability, complicated fabrication processes, and low producing efficiency, owing to the thermodynamic instability of metastable materials and the heuristic principles for preparing metastable materials. Moreover, conventional methods, such as rapid quenching, mechanical alloying, pulse laser deposition, hydrothermal synthesis and the sol-gel method, are employed for producing various metastable materials as well [ 12 ]. However, these methods encounter challenges such as limited particle size, high energy consumption, complex equipment requirements, long processing time, difficulties in achieving uniform size and distribution, and environmental concerns.…”
Section: Introductionmentioning
confidence: 99%